CLIMATIC ASPECTS RELATED TO THE DISTRIBUTION OF BRAZILIAN PINE IN THE STATE OF SANTA CATARINA - Fritzsons, Elenice; Wrege, Marcos Silveira; Mantovani, Luiz Eduardo (Floresta, 2018)
The natural presence of Araucaria angustifolia (Bert) O. Kuntze is associated with several climatic aspects, but the relative importance of each of them has not been sufficiently explored yet. The objective of this study was to identify climatic aspects that are most related to the presence of the species in the state of Santa Catarina, Brazil. For this purpose, meteorological stations from the municipalities were separated into: places with records of natural occurrence of araucaria; and places without records of the species. Temperature, precipitation and insolation data from these stations were employed, and they were subjected to several univariate and multivariate statistical tests to identify the climates in which araucaria preferentially develop. All the areas presented surplus water, and the insolation hours did not present significant differences. The areas where the araucaria occurred were also separated into three subgroups: two in the Southern Plateau; and one in the highest western sides of the state. These areas were climatically different regarding precipitation, evapotranspiration, and water availability. Finally, we concluded that the araucaria occurs in places where the average temperatures are lower and the annual rainfall and the winter period rainfall are higher. The results generated by cluster analysis indicated the prospection conditions for in situ conservation purposes. Also, it would assist in the elaboration of breeding programs.